Layer-by-Layer Nanoparticles for Calcium Overload in situ Enhanced Reactive Oxygen Oncotherapy - Zhang B; Man J; Guo L; Ru X; Zhang C; Liu W; Li L; Ma S; Guo L; Wang H; Wang B; Diao H; et al. (International Journal of Nanomedicine, 2024)
Boye Zhang,1,2 Jianliang Man,3,4 Lingyun Guo,1 Xiaoxia Ru,1 Chengwu Zhang,1,2 Wen Liu,1,2,5 Lihong Li,1,2,5 Sufang Ma,1,2 Lixia Guo,2,4 Haojiang Wang,1,2 Bin Wang,1,2 Haipeng Diao,1,5 Renchao Che,6,7 Lili Yan1,2,5 1School of Basic Medical Sciences, Shanxi Medical University, Taiyuan, 030001, People’s Republic of China; 2Shanxi Province Brain Degenerative Diseases Precision Diagnosis and Treatment Engineering Research Center, Shanxi Medical University, Jinzhong, 030606, People’s Republic of China; 3Academy of Medical Sciences, Shanxi Medical University, Taiyuan, 030001, People’s Republic of China; 4College of Pharmacy, Shanxi Medical University, Taiyuan, 030001, People’s Republic of China; 5Key Laboratory of Cellular Physiology, Ministry of Education, Shanxi Medical University, Taiyuan, 030001, People’s Republic of China; 6Laboratory of Advanced Materials, Shanghai Key Laboratory of Molecular Catalysis and Innovative Materials, Academy for Engineering &Technology, Fudan University, Shanghai, 200438, People’s Republic of China; 7Zhejiang Laboratory, Hangzhou, 311100, People’s Republic of ChinaCorrespondence: Lili Yan; Renchao Che, Email yanlili@sxmu.edu.cn; rcche@fudan.edu.cnBackground: Challenges such as poor drug selectivity, non-target reactivity, and the development of drug resistance continue to pose significant obstacles in the clinical application of cancer therapeutic drugs. To overcome the limitations of drug resistance in chemotherapy, a viable treatment strategy involves designing multifunctional nano-platforms that exploit the unique physicochemical properties of tumor microenvironment (TME).Methods: Herein, layer-by-layer nanoparticles with polyporous CuS as delivery vehicles, loaded with a sonosensitizer (tetra-(4-aminophenyl) porphyrin, TAPP) and sequentially functionalized with pH‐responsive CaCO3, targeting group hyaluronic acid (HA) were designed and synthesized for synergistic treatment involving chemodynamic therapy (CDT), sonodynamic therapy (SDT), photothermal therapy (PTT), and calcium overload. Upon cleavage in an acidic environment, CaCO3 nanoparticles released TAPP and Ca2+, with TAPP generating 1O2 under ultrasound trigger. Exposed CuS produced highly cytotoxic ·OH in response to H2O2 and also exhibited a strong PTT effect.Results: CuS@TAPP-CaCO3/HA (CTCH) delivered an enhanced ability to release more Ca2+ under acidic conditions with a pH value of 6.5, which in situ causes damage to HeLa mitochondria. In vitro and in vivo experiments both demonstrated that mitochondrial dysfunction greatly amplified the damage caused by reactive oxygen species (ROS) to tumor, which strongly confirms the synergistic effect between calcium overload and reactive oxygen therapy.Conclusion: Collectively, the development of CTCH presents a novel therapeutic strategy for tumor treatment by effectively responding to the acidic TME, thus holding significant clinical implications.Keywords: mitochondria damage, calcium overload, reactive oxygen oncotherapy, pH-responsive, synergistic treatment